Internalizing Patience and Gratitude in Q.S. Ibrahim, Verse 7, for the Mental Health of Teenagers in the Digital Era - Mita Sari; Rosdialena (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Mental health issues have become a critical challenge for adolescents in the digital era. Academic pressure, massive social media exposure, and social comparison behavior frequently trigger anxiety, insecurity, and depression among the younger generation. This study aims to formulate a framework for adolescent mental health education by integrating the concepts of patience (sabar) and gratitude (syukur) contained in Q.S. Ibrahim Verse 7. The research methodology employed is library research with a qualitative-descriptive approach. Primary data sources were obtained from standard exegesis (tafsir) books, while secondary data were sourced from psychological literature and related mental health journals. The results indicate that the command of gratitude in Q.S. Ibrahim verse 7 psychologically functions as a mechanism of positive appraisal and internal validation that effectively counteracts digital social comparison. Meanwhile, patience is implemented as an active coping mechanism to build psychological resilience when facing life stressors. The integration of these two Qur'anic values establishes a spiritual-based mental health education framework (Islamic Mindfulness) applicable to modern adolescents.